Kant e l'ortodossia russa Accademie ecclesiastiche e filosofia in Russia tra XVIII e XIX secolo - POZZI, VERA (Premio Istituto Sangalli per la storia religiosa, 2017)
The diffusion of Kantian philosophy in the Russian culture was a singularly early event: even the Orthodox ecclesiastical Academies were involved in this process, despite the control exercised by the censorship in defense of the metaphysical and theological tradition. The history and sources of the "philosophy of ecclesiastical academies" are also examined through the analysis of the works of two authors (I.Ja. Vetrinskij and P.D. Jurkevic), who, with their reaction to the Kantian "revolution", attested to the deep awareness of the necessity of a real confrontation with criticism. This investigation is completed by an appendix dedicated to the complex events of Kantian studies in the Russian language during the decades marked by the Soviet regime.